Emergence of a Recombinant Bovine Enterovirus in China: Insights from Phylogenetic and Temporal Analysis - Guidan Feng; Taisheng Kang; Pan Tang; Caihua Xie; Ruoqian Yan; Weidong Qian (Animals)
Bovine enteroviruses (BEVs) are emerging pathogens with poorly understood evolutionary dynamics and zoonotic potential. Here, we report the discovery of a novel recombinant BEV strain, HeN-2022, isolated from cattle in China. Genomic analysis revealed that HeN-2022 is a primary hybrid of BEV-E1 (VG527, Ireland) and BEV-E4 (GX1901, China), with recombination breakpoints in the VP1 gene and 5′ UTR. Divergence dating traced its origin to 1991, predating closely related strains. Experimental infection in sheep demonstrated asymptomatic viral shedding (peak at 5 dpi) and robust neutralizing antibody responses, highlighting the potential cross-species adaptability. These findings underscore recombination as a potential key driver of BEV evolution and emphasize the need for global surveillance to address emerging livestock pathogens.